Effects of the COVID-19 pandemic on working conditions and mental health among employees in health and social services - Claudia Peters; Madeleine Dulon; Jan Felix Kersten; Christofer Hartung; Albert Nienhaus; Anja Schablon (Frontiers in Public Health, 2026)
Background The COVID-19 pandemic has posed major challenges in the workplace. This exploratory, cross-sectional study investigated the association between occupational activities and mental health. Methods In 2023, 576 employees from health and social care institutions were surveyed about their occupational situation, their self-assessed ability to work, health-related issues, as well as their mental health and quality of life. Results The respondents were predominantly women with an average age of 49 years. Of these, 59% were healthcare workers (HCWs), such as nurses, physicians and therapists. The non-healthcare group mainly consisted of people working in educational or care-related professions, as well as administrative staff. In comparison, HCWs reported poorer work ability (mean 6.9 vs. 7.3) and described a work situation characterized by emotional strain, time pressure and work-privacy conflict. They were also more likely to consider changing jobs or leaving their profession. Around one-fifth of all respondents suffered from moderate to severe mental distress. HCWs also reported symptoms of depression more frequently and a lower quality of mental life. Conclusion Employees in medical professions were under considerable strain due to their work during the pandemic. Therefore, the prevention of high levels of mental stress should play a key role in maintaining and strengthening long-term mental health.